Penerapan GTMetrix Dan K6 Dalam Pengujian Performa Dan Tingkat Stress Pada Website POS (Point Of Sale) (Studi Kasus Website waroeng99 ) - Pujo Hari Saputro (Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
The development of technology which continues to increase day by day has an impact in various fields, especially in the field of sales. It has been proven that there have been many developments in sales services or services carried out online (E-commerce). in this case, of course, requires an application to process data and transactions, one of which is "waroeng99". waroeng99 is a POS (point of sale) website that is used for management and recording buying and selling transactions online. With the increase in the use of services on this website, a test was carried out using the GTMetrix and LoadImpact (K6) websites to test the performance and stress levels on the website. So that you can find several problems on the waroeng99 website.